Influence of fermentation level and geographical origin on cocoa bean oligopeptide pattern. (15th November 2016) - Caligiani, Augusta; Marseglia, Angela; Prandi, Barbara; Palla, Gerardo; Sforza, Stefano
Highlights: An overview on the peptide pattern of different cocoa samples is provided. Peptide pattern and amount are strictly related to the fermentation process. Ratio of peptides from vicilin and from cocoa albumin can be proposed as fermentation marker. Some peptides are characteristic of specific geographic origin/varieties. Abstract: Peptides and amino acids generated during cocoa bean fermentation are the most important precursors for the development of cocoa aroma, however cocoa oligopeptide fraction is under-investigated. In this study, we perform a deep investigation of the presence of oligopeptides in unfermented, under fermented, and well-fermented cocoa beans from all of the main producing countries, with the aim to obtain a better definition of cocoa quality and a deeper comprehension of biochemical changes occurring during fermentation. Oligopeptides were determined by UPLC/ESI-MS and 35 low-molecular weight peptides were identified and subjected to semi-quantitative analysis. Results showed that fermented cocoas can be differentiated from unfermented cocoas by their possession of a higher total amount of oligopeptides and a lower ratio of vicilin to 21 kDa cocoa seed albumin peptides. A variability in the peptide pattern was observed also among well-fermented cocoa samples of different geographical origin, suggesting diversified proteolytic activities.